Referral to and engagement in substance use disorder treatment within opioid intervention courts in New York: a qualitative study of implementation barriers and facilitators - Megan A. O'Grady; Katherine S. Elkington; Gail Robson; Ikenna Y. Achebe; Arthur Robin Williams; Alwyn T. Cohall; Renee Cohall; Monica Christofferson; Alejandra Garcia; Kelly S. Ramsey; Pat Lincourt; Susan Tross (BMC, 2024)
Abstract Background People with opioid use disorder (OUD) are frequently in contact with the court system and have markedly higher rates of fatal opioid overdose. Opioid intervention courts (OIC) were developed to address increasing rates of opioid overdose among court defendants by engaging court staff in identification of treatment need and referral for opioid-related services and building collaborations between the court and OUD treatment systems. The study goal was to understand implementation barriers and facilitators in referring and engaging OIC clients in OUD treatment. Methods Semi-structured interviews were conducted with OIC stakeholders (n = 46) in 10 New York counties in the United States, including court coordinators, court case managers, and substance use disorder treatment clinic counselors, administrators, and peers. Interviews were recorded and transcribed and thematic analysis was conducted, guided by the Exploration, Preparation, Implementation, Sustainment (EPIS) framework, employing both inductive and deductive coding. Results Results were conceptualized using EPIS inner (i.e., courts) and outer (i.e., OUD treatment providers) implementation contexts and bridging factors that impacted referral and engagement to OUD treatment from the OIC. Inner factors that facilitated OIC implementation included OIC philosophy (e.g., non-punitive, access-oriented), court organizational structure (e.g., strong court staff connectedness), and OIC court staff and client characteristics (e.g., positive medications for OUD [MOUD] attitudes). The latter two also served as barriers (e.g., lack of formalized procedures; stigma toward MOUD). Two outer context entities impacted OIC implementation as both barriers and facilitators: substance use disorder treatment programs (e.g., attitudes toward the OIC and MOUD; operational characteristics) and community environments (e.g., attitudes toward the opioid epidemic). The COVID-19 pandemic and bail reform were macro-outer context factors that negatively impacted OIC implementation. Facilitating bridging factors included staffing practices that bridged court and treatment systems (e.g., peers); barriers included communication and cultural differences between systems (e.g., differing expectations about OIC client success). Conclusions This study identified key barriers and facilitators that OICs may consider as this model expands in the United States. Referral to and engagement in OUD treatment within the OIC context requires ongoing efforts to bridge the treatment and court systems, and reduce stigma around MOUD.